2015
DOI: 10.1080/00103624.2015.1011747
|View full text |Cite
|
Sign up to set email alerts
|

Response of Diploid Perennial Ryegrass to Fungal Endophyte AR29 Infections under Water Stress

Abstract: Asexual fungus Neotyphodium spp. are often associated with aboveground parts of different grasses. Perennial ryegrass (Lolium perenne L.), dominant cool-season grass species in New Zealand, is frequently infected by endophytic fungus (Neotyphodium lolli). To evaluate the growth, nutrient status, and avoidance to dehydration stress, clones of diploid perennial ryegrass either infected with Neotyphodium lolii AR29 endophyte (E+) or not infected (E−) were grown in a potted Andisol with intermittent wetting-drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This result is in line with several other studies showing a neutral effect of fungal endophytes on shoot biomass under stress (Briggs et al, 2013;He L, 2017;Hesse et al, 2003Hesse et al, , 2005Hill et al, 1996;Jia et al, 2015;Kane, 2011;Khan et al, 2013;Oberhofer et al, 2014;Rudgers and Swafford, 2009). In contrast, certain endophytic strains were also reported to increase (Ghabooli et al, 2013;Gibert et al, 2012;Hill et al, 1996;Malinowski et al, 2005;Vazquez-de-Aldana et al, 2013;Zhang and Nan, 2007) or decrease (Assuero et al, 2006;He L, 2017;Rahman et al, 2015;Yang et al, 2014; plant shoot biomass under water stress. Previously, we reported increased shoot biomass increased of N. benthamiana plants under stress when inoculated with the same fungal strains that we used in the present study (Dastogeer et al, 2017a).…”
Section: Plant Responses To Water Stresssupporting
confidence: 92%
“…This result is in line with several other studies showing a neutral effect of fungal endophytes on shoot biomass under stress (Briggs et al, 2013;He L, 2017;Hesse et al, 2003Hesse et al, , 2005Hill et al, 1996;Jia et al, 2015;Kane, 2011;Khan et al, 2013;Oberhofer et al, 2014;Rudgers and Swafford, 2009). In contrast, certain endophytic strains were also reported to increase (Ghabooli et al, 2013;Gibert et al, 2012;Hill et al, 1996;Malinowski et al, 2005;Vazquez-de-Aldana et al, 2013;Zhang and Nan, 2007) or decrease (Assuero et al, 2006;He L, 2017;Rahman et al, 2015;Yang et al, 2014; plant shoot biomass under water stress. Previously, we reported increased shoot biomass increased of N. benthamiana plants under stress when inoculated with the same fungal strains that we used in the present study (Dastogeer et al, 2017a).…”
Section: Plant Responses To Water Stresssupporting
confidence: 92%
“…However, plants respond to drought stress through physiological, biochemical, and morphological responses, culminating in stress tolerance. Many studies showed that the endophytes of the genus Epichloë play an important function in enhancing drought resistance in Epichloë-infected grasses through regulating the photosynthetic, osmotic adjustment, and antioxidant enzyme systems, water use efficiency, and nutrient accumulation. , , Studies with A. inebrians have demonstrated that E.…”
Section: Influence Of Epichloë Endophytes On Host Grass Under Abioti...mentioning
confidence: 99%
“…Many studies showed that the endophytes of the genus Epichloëplay an important function in enhancing drought resistance in Epichloe-infected grasses through regulating the photosynthetic, osmotic adjustment, and antioxidant enzyme systems, water use efficiency, and nutrient accumulation. 12,[22][23][24][25][26][27][28][29][30][31][32][33][34]56 Studies with A. inebrians have demonstrated that E. gansuensis infection (E+) increased proline accumulation and decreased superoxide dismutase (SOD) activity compared to plants without this E. gansuensis (E−) when under drought stress; however, photosynthetic capacity of E+ and E− A. inebrians plants does not differ when under drought stress. 57 The presence of an Epichloëspp.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutual relationships have been found between endophytes and some important cultivated grasses such as tall fescue and perennial ryegrass [22][23][24]. The host plants can provide endophytic fungi with photosynthetic products, nutrients and habitats; moreover, secondary metabolites produced by endophytic fungi can promote the growth and development of host plants [25] and improve the host's resistance to biotic [26][27][28][29][30] and abiotic stresses [31][32][33] such as drought [34][35][36], nutrient deficiency [37], herbivory [38][39][40][41] and pathogens [25,42,43], Given the higher growth advantages of endophyte-infected (E+) over endophyte-free (E−) plants, E+ grasses are considered to be ideal plant species for artificial grasslands. However, endophyte infection could change the interspecific relationship between host grasses and neighboring plants [44].…”
Section: Introductionmentioning
confidence: 99%